PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK KELAS VI SD N 3 BANCARKEMBAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING TERINTEGRASI MEDIA KONKRIT MATERI ASEAN - Mariyatul Qibtiyah; Ani Irawati; Subuh Anggoro (Journal of Professional Elementary Education, 2023)
Social Studies (IPS) is not merely a subject focused on memorization; rather, it aims to provide knowledge and understanding of facts and materials that should be retained and implemented to cultivate a sense of responsibility within the context of community, nation, and state. The objective of this research is to improve the learning achievement of Grade VI students at SD N 3 Bancarkembar regarding ASEAN through the integration of gamified problem-based learning. This study falls under the category of Classroom Action Research (CAR). The research subjects consist of 21 students in Class VI-B. Data were collected through multiple-choice tests and subsequently analyzed using descriptive statistics. The research results demonstrate an improvement in learning achievement in each cycle. The pre-cycle achievement rate was 9.52% with an average score of 31.43, while in Cycle 1, it increased to 57.14% with an average score of 74.5, and in Cycle 2, it reached 66.66% with an average score of 79.57. These findings substantiate that the implementation of the problem-based learning model integrated with concrete media can enhance the learning achievement of ASEAN-related material in Grade VI at SD N 3 Bancarkembar